Investigating resistance in clinical Mycobacterium tuberculosis complex isolates with genomic and phenotypic antimicrobial susceptibility testing: a multicentre observational study - Finci, Iris; Albertini, Audrey; Merker, Matthias; Andres, Sönke; Bablishvili, Nino; Barilar, Ivan; Cáceres, Tatiana; Crudu, Valeriu; Gotuzzo, Eduardo; Hapeela, Nchimunya; Hoffmann, Harald; Hoogland, Christine; et al. (The lancet. Microbe, 2022)
Background Whole-genome sequencing (WGS) of Mycobacterium tuberculosis complex has become an important tool in diagnosis and management of drug-resistant tuberculosis. However, data correlating resistance genotype with quantitative phenotypic antimicrobial susceptibility testing (AST) are scarce.
Online verfügbar: 27. July 22, Artikelversion: 1. September 2022
Gesehen am 20.03.2023